Essential factors towards optimal utilisation of construction resources. Issue 4 (22nd August 2014) - Fapohunda, Julius Ayodeji; Chileshe, Nicholas
Abstract : Purpose: The capability of controlling and monitoring construction resources and the application of production information to achieve predetermined objectives of scope, cost, time, quality, and clients' satisfaction are the primary function of site managers. However, the effective implementation of this production information is usually hindered by some factors that often results in various conscious, unconscious, or unavoidable resource wastage. Thus, this paper evaluates and presents the essential factors that will enhance site managers' efficient performance which will perpetuate optimal construction resources utilisation. Design/methodology/approach: The research is triangulated. The investigations are based on an action survey, comprising structured quantitative questionnaires and qualitative interview surveys conducted with some project managers in the UK construction industry. Findings: The research evaluates problems associated with the site managers' on project delivery and establishes essential factors towards efficient resources utilisation. Among the identified predicaments are the design team attitudes towards site managers' corrections, modification and alterations; communication gap between the design and construction teams; and production information inadequacy. Thus, the factors identified which will enhance the efficiencies of the site managers are communication effectiveness and effective information dissemination, conducive environment, production information simplicity and explicitness, in addition to skilled workers participation in knowledge transfer and sharing, to mention but a few. Originality/value: The facts presented in this study will significantly enhance site managers' optimal resources utilisation, and provide the opportunity for construction resources waste minimisation. Thus, the adequate implementation of the innovative measures presented in this study will not only enhance the performance of site managers on resources utilisation, but will also augment client satisfactions.